SEISMICITY AND SEISMOTECTONIC STUDY FOR ALTUNKOPRI DAM SITE NORTH IRAQ - Alridha, N.; Baqir, R.; Hamid, A. (Iraqi Journal of Science, 2024)
A seismicity and seismotectonicstudy for a dam site located on latitude (35˚:48΄ – 35˚:50΄) degree North and longitude (44˚:20΄) degree East was carried out. The surrounding area within a circular area ofradius 100 km was also included to determine the seismic activity.It is found that the area was subjected to 10 historical events prior 1900 year with an intensity ranges (V - IX) degree and the area exposed to about 163 recent earthquakes with Ms=1.1 – 5.9.The maps of epicentral locations, tectonic features and lineaments of the study area were compiled and drawn. Matching was carried out for these three maps and it is found that most of earthquake epicenters coincide with the main structural and tectonic phenomena at the dam site.ISO – intensity map for the dam site was also drawn. It is found that the dam site was located between (5 -6) degree earthquake intensity on MMI Scale